Growth performance and carcass traits of young nellore bulls supplemented with or without addition of lipids - Clóvis Carlos Silveira Filho; Carlos Augusto de Alencar Fontes; Elizabeth Fonsêca Processi; Laila Cecília Ramos Bendia; Paulo Roberto Silveira Pimentel; Ronaldo Lopes Oliveira; Leilson Rocha Bezerra; Isabelle Batista Santos; Tiago Cunha Rocha (Bioscience Journal, 2020)
The aim of research was to evaluate the performance and characteristics of the carcasses of Nellore young bulls in grazing supplemented with or without addition of lipids. Twenty–eight young bulls, 301 ± 5.8 kg in body weight, which four constituted the reference group and the twenty-four remnants were used in the experiment and randomly distributed into four groups according to treatment: only Panicum maximum cv. Mombasa grass; Mombasa grass with concentrated supplementation based on soybean meal; Mombasa grass with concentrate containing lipids from soybean oil; and Mombasa grass with concentrate containing lipids derived from soybean grains. The total dry matter intake of the animals fed only Mombasa grass did not differ from the average intake of the three treatments supplemented with concentrate. There were no differences (P>0.05) between Mombasa grass and diets with concentrate, supplementation with or without lipid and lipids sources in the carcass traits, gastrointestinal tract, organs and loin eye area. Nellore bulls receiving concentrate increased subcutaneous fat thickness compared with bulls that received only Mombasa grass. Nellore young bulls fed Mombasa grass only, supplemented with or without addition of lipids were similar regarding growth performance and carcass traits.